2000
DOI: 10.1007/s004250050052
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biosynthesis of 1,4-β-galactan attached to rhamnogalacturonan I

Abstract: The biosynthesis of galactan was investigated using microsomal membranes isolated from suspension-cultured cells of potato (Solanum tuberosum L. var. AZY). Incubation of the microsomal membranes in the presence of UDP-[14C]galactose resulted in a radioactive product insoluble in 70% methanol. The product released only [14C]galactose upon acid hydrolysis. Treatment of the product with Aspergillus niger endo-1,4-beta-galactanase released 65-70% of the radioactivity to a 70%-methanol-soluble fraction. To a minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
(21 reference statements)
3
40
0
Order By: Relevance
“…Gunter and Ovodov, (2002) observed that polysaccharides in Silene vulgaris callus is the primary metabolite (polysaccharide) cell wall component permanently biosynthesized through cells. Therefore, the results presented here are consistent with those of Geshi et al, (2000); Goubet and Morvan, (1994). These studies reported that polysaccharides have important roles in the expansion phase and cell division.…”
Section: Biochemical Estimationsupporting
confidence: 92%
“…Gunter and Ovodov, (2002) observed that polysaccharides in Silene vulgaris callus is the primary metabolite (polysaccharide) cell wall component permanently biosynthesized through cells. Therefore, the results presented here are consistent with those of Geshi et al, (2000); Goubet and Morvan, (1994). These studies reported that polysaccharides have important roles in the expansion phase and cell division.…”
Section: Biochemical Estimationsupporting
confidence: 92%
“…Most likely, one or two as yet unidentified galactosyltransferases are required to initiate the b-1,4-galactan side chains. This activity has been described in an extract from potato that could initiate but not elongate b-1,4-galactan side chains in vitro (Geshi et al, 2000). Future studies should clarify this but will require a set of putative oligosaccharide substrates that are not easily obtained.…”
mentioning
confidence: 86%
“…The assays have been further developed with solubilization of the membranes and the use of exogenous acceptors (Geshi et al, 2000(Geshi et al, , 2002Peugnet et al, 2001;Ishii et al, 2004). Activities were found in flax (Linum usitatissimum; Peugnet et al, 2001) and potato (Geshi et al, 2002) that could transfer Gal from UDP-Gal onto RGI acceptors, resulting in products that could be digested with galactosidase but not with endo-b-1,4-galactanase.…”
Section: Rgimentioning
confidence: 99%